Investigation of the Aquifer Protective Capacity and Groundwater Quality around Some Open Dumpsites in Sapele Delta State, Nigeria - Julius Otutu Oseji; James Chucks Egbai; Emmanuel Chukwuemeka Okolie; Etebefia Chris Ese (Applied and Environmental Soil Science)
Aquifer protective capacity and groundwater quality investigations around some open dumpsites were conducted along New Road Sapele, Delta State. Nine Schlumberger arrangements of vertical electrical soundings (VES) were carried out with a maximum electrode separation of 500 m, and obtained data were interpreted by partial curve matching and computer iteration using Win Resist software. 2D survey using nine dipole-dipole stations was also utilized to give resistivity map of the dumpsites, while standard laboratory methods were used to analyze the groundwater. The study shows four to five geoelectric sections. The aquifer is within the third, fourth, and fifth layers at a depth of 30 m. The overburden protective capacity from the total longitudinal unit conductance indicates that VES 1 and 5 are adequately protected with protective capacity of 0.7 to 0.9 mhos, VES 2, 3, 6, and 7 are moderately protected with conductance values of 0.2 to 0.69 mhos, VES 4 is weakly protected with values of 0.12 mhos, and VES 8 and 9 are poorly protected with values of 0.003 to 0.004 mhos. In the 2D imaging, VES 4, 8, and 9 show contaminant presence to the depth of 20 m while VES 3, 6, and 7 show contamination to a depth of 50 m. However, the aquifer shows good transmissivity, an indication that if it is contaminated, the contaminants will circulate the aquifer at a high rate. The groundwater flows in the northeast (NE) direction, thereby recharging river Ethiope. The study also shows the presence of lead (0.01 mg/l), nickel (0.02 mg/l), and cadmium (0.03 mg/l), which made it unsafe for drinking and use in other life-related activities. Groundwater should hence be sourced from a depth of about 45–50 m in order to tap from the uncontaminated aquifer.